Retracted: A study of predictive factors of malignancy in thyroid nodules - Umapathy, P.; Swaminathan, G. Ashok; Farshana, M. Fathima; Devagi, M. (International Surgery Journal, 2018)
The article titled, "A study of predictive factors of malignancy in thyroid nodules", published in the International Surgery Journal, Volume 5, Issue 12, 2018, Pages 3817-3822, DOI: http://dx.doi.org/10.18203/2349-2902.isj20184712 is being retracted. We received complaint after publication of the article that it’s a plagiarized and fabricated work from an unpublished thesis submitted to the university. We contacted the corresponding author Dr. G. Ashok Swaminathan and he agreed to retract the article.